O impacto da infeção por SARS-Cov-2 nos desfechos materno, embriofetal e neonatal. O que sabemos? - Marta Alexandra Bezerra Monteiro de Aguiar (2023)
Research Question: Identify topics of interest pertaining to the impact of the SARS-Cov-2 virus infection in pregnant women, embryos, foetuses and neonates. Methods: A literature review was conducted on the impact of SARS-Cov-2 infection on the pregnant woman, embryo, foetus and neonate. The studies obtained were further categorized by type of outcome. The outcomes considered were: need for maternal admission to the ICU, need for maternal invasive/non-invasive oxygen support, maternal hospitalization, maternal death, preterm birth, small for gestational age, abortion, foetal death and foetal growth restriction. Results: After the literature review, 20 studies were included in these analysis. Of these, 11 focused on maternal outcomes and 18 on embryofoetal and neonatal outcomes (9 studies related to both). Conclusion: SARS-Cov-2 infection is associated with adverse maternal outcomes, such as ICU admission and oxygen support. More research is needed, particularly on the risk of adverse embryofoetal and neonatal outcomes.